City Branding Performance Analysis of 'Flower City' to Increase the Tourist Visit Interest in Tomohon City - Mercy Reinette Handayani Mantur; Pricilia Anastasia Chuanda (Quantitative Economics and Management Studies, 2023)
Tomohon City is a city known as "Kota Bunga" or Flower City as a tourist city located in North Sulawesi Province, Indonesia. Based on data from the Central Statistics Agency (BPS) of Tomohon City in 2021, as many as 75% of tourists stated that they were interested in visiting this city because of the city branding as "Flower City". However, only around 60% of tourists are satisfied with the quality of its tourism services and facilities. This research aims to analyze the performance of city branding of Tomohon City whether it is in line with expectations according to tourists' assessments so that indicator results are able to be improved and maintained. This research was conducted in Tomohon City, North Sulawesi Province, consisted of two hundred respondents from among tourists to fill out the questionnaire and five respondents from the government and stakeholders for interviews through the sampling technique, namely purposive sampling. The method in this research used Importance Performance analysis, which was then analyzed in the Importance Performance Matrix based on the Cartesian quadrant. The results of this research are based on the importance of performance matrix. Tourism potential indicators are the indicators in quadrant 1, which are considered the most important but have not shown performance that satisfies visitors, causing them to be a priority for improvement. Meanwhile, the attractiveness indicator is in quadrant 2, which means that this indicator is considered important and able to satisfy visitors. The city atmosphere and accommodation indicators are included in quadrant 3 where the performance level of both indicators is low and is considered very unimportant. City physical indicators and community openness are included in quadrant 4 where these indicators are considered unimportant enough and are not expected but have high performance.